Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/smll.202200822
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Poly(Vinylidene Fluoride‐Co‐Hexafluoropropylene) Loaded 3D Marigold Flower‐Like Bismuth Tungstate Triboelectric Films for Mechanical Energy Harvesting and Sensing Applications

Abstract: Triboelectric nanogenerators (TENGs) are one of the most trending energy harvesting devices because of their efficient and simple mechanism in harvesting mechanical energy from the environment into electricity. Herein, ferroelectric and dielectric bismuth tungstate (Bi2WO6 (BWO)) with a marigold flower‐like structure is prepared via a hydrothermal method, which is embedded in poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP), forming a PVDF‐HFP/BWO composite polymer film (CPF) to fabricate TENGs. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 75 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…The decrease in the electrical performance is presumably due to the agglomeration of the BST-2 inside the composite film as shown in the FE-SEM images of composite films in Figure S7, Supporting Information. [10] The agglomeration of the MPs leads to the unevenly applied force and resistance to align dipoles in a particular direction within the composite film. [39,40] From the electrical measurement of various HNGs, it is observed that the HNG with 10 wt% BST-2/PDMS composite film produces maximum electrical performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the electrical performance is presumably due to the agglomeration of the BST-2 inside the composite film as shown in the FE-SEM images of composite films in Figure S7, Supporting Information. [10] The agglomeration of the MPs leads to the unevenly applied force and resistance to align dipoles in a particular direction within the composite film. [39,40] From the electrical measurement of various HNGs, it is observed that the HNG with 10 wt% BST-2/PDMS composite film produces maximum electrical performance.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Meanwhile, loading perovskite particles having a very high dielectric constant or ferroelectricity/piezoelectricity into a polymer film could potentially enhance its dielectric constant, thus resulting in improved electrical output. [10,11] Herein, the fabricated device was named a hybrid nanogenerator (HNG) due to the hybridization of piezoelectric and triboelectric effects. Along with the development of an improved triboelectric film to efficiently convert mechanical energy into electricity, the device structure of HNG is also important to maximize its utilization to harvest various mechanical motions into electricity.…”
mentioning
confidence: 99%
“…Consequently, the instantaneous and effective power density can be calculated using the following equation. [21] W eff =…”
Section: Resultsmentioning
confidence: 99%
“…However, to increase the charge transfer properties of PVDF and to produce high-performance PVDF-based TENG devices, it is important to incorporate dielectric and electroactive fillers. [18][19][20][21][22][23] To enhance the triboelectric behaviors of PVDF and its copolymers, several functional nanocomposite fillers, such as graphene quantum dots, carbon nanotubes, and silver nanowires, have been incorporated. [24] Recently, 2D Ti 3 C 2 T xbased MXene materials have attracted attention in the energy harvesting and storage fields.…”
Section: Introductionmentioning
confidence: 99%
“…10i) embedded in poly(vinylidene fluoride- co -hexafluoropropylene) (PVDF-HFP) film is also prepared, which not only results in high dielectric constant, but also increases the β-phase crystallization of the polymer. 168 The CaCu 3 Ti 4 O 12 (CCTO) particles with a cubic perovskite structure and high permittivity (up to 7500) are introduced into the positive BMF film to enhance internal polarization and output performance (Fig. 10j).…”
Section: Inorganic/organic Composite Materialsmentioning
confidence: 99%